2017
DOI: 10.1016/j.bcp.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Roscovitine attenuates intimal hyperplasia via inhibiting NF-κB and STAT3 activation induced by TNF-α in vascular smooth muscle cells

Abstract: Roscovitine is a selective CDK inhibitor originally designed as anti-cancer agent, which has also been shown to inhibit proliferation in vascular smooth muscle cells (VSMCs). However, its effect on vascular remodeling and its mechanism of action remain unknown. In our study, we created a new intimal hyperplasia model in male Sprague-Dawley rats by trypsin digestion method, which cause to vascular injury as well as the model of rat carotid balloon angioplasty. Roscovitine administration led to a significant red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…IL-6 and IL-1 β , two typical proinflammatory cytokines, play important roles in the inflammatory response [ 36 ]. MCP-1, a vital proinflammatory cytokine, is directly involved in the transformation of monocytes into macrophages [ 37 ]. Low-dose alcohol reportedly has anti-inflammatory effects [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 and IL-1 β , two typical proinflammatory cytokines, play important roles in the inflammatory response [ 36 ]. MCP-1, a vital proinflammatory cytokine, is directly involved in the transformation of monocytes into macrophages [ 37 ]. Low-dose alcohol reportedly has anti-inflammatory effects [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…16 In response to vascular injury, VSMCs will engage in phenotypic regulation featuring augmented inflammation, proliferation, and migration; thus, they form a neointima. 1 Proinflammatory cytokines are pivotal regulators of arterial inflammation and intimal hyperplasia, and they participate in pathological vascular remodeling. 17 The present study demonstrated that PDGF-BB induced VSMC proliferation and migration, accompanied by increased secretion of inflammatory factors, including IL-1b, IL-6, and TNF-a, which was consistent with the previous study by Pi et al 18 However, these noticeable facilitating effects on the VSMC proliferative phenotype and inflammation were largely abolished by KCNQ1OT1 overexpression, implying an enormous potential of KCNQ1OT1 as an effective target in the treatment of intimal hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Intimal hyperplasia is a common phenomenon that occurs in the process of artery remodeling after vascular injury, and it is often observed in the treatment of various vascular diseases, such as atherosclerosis, angioplasty, stent implantation, and bypass operation. 1,2 In response to vascular injury, vascular smooth muscle cells (VSMCs) can undergo increased inflammation, proliferation, and migration, as well as decreased expression of smooth muscle markers, developing into intimal hyperplasia. 3 Therefore, inhibiting the proliferation and inflammation of VSMCs is a crucial step in delaying vein graft (VG) intimal hyperplasia, and research on the regulatory mechanism of the function and phenotype of VSMCs is desperately needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abnormal proliferation and oxidative stress of VSMC play an important role in the occurrence and development of vascular remodeling ( 24 , 25 ). Evidence is also emerging to suggest that treatment of proliferation and oxidative stress of VSMC causes a reduction or prevents the progression of the carotid intima-media thickness, paralleled by a decrease in cardiovascular risk and events ( 26 , 27 ). Therefore, exploring an effective treatment strategy to block the proliferation of VSMC and the occurrence of oxidative stress is essential for the treatment of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%